The role of BMP4 in adipose-derived stem cell differentiation: A minireview - Setiawan, Abdul Malik; Kamarudin, Taty Anna; Abd Ghafar, Norzana (Frontiers in Cell and Developmental Biology, 2022)
Bone morphogenetic protein 4 (BMP4) is a member of the transforming growth factor beta (TGF-β) superfamily of cytokines responsible for stem cells' commitment to differentiation, proliferation, and maturation. To date, various studies have utilized BMP4 as a chemical inducer for in vitro differentiation of human Mesenchymal Stem Cells (MSCs) based on its potential. BMP4 drive in vitro differentiation of ADSC via TGF- signaling pathway by interacts with BMP receptors leading to the activation of smad-dependent and smad-independent pathways. The BMP4 signaling pathways are regulated by intracellular and extracellular BMP4 antagonist. Extracellular BMP4 antagonist prevent interaction between BMP4 ligand to its receptors, while intracellular BMP4 antagonist shutdown the smad-dependent pathways through multiple mechanism. BMP4 proved as popular differentiation factors to induce ADSC differentiation into cell from mesodermal origin. However, addition of all-trans retinoic acid is needed in trans-differentiation of ADSC into ectodermal lineage cells. Suggesting that signaling pathways may be necessary to be activated for in vitro trans-differentiation of ADSC.